2020
DOI: 10.1093/alcalc/agaa071
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Gender Differences in Alcohol Treatment

Abstract: Aims Alcohol consumption is a threat to health worldwide and leads to substantial expenses for society. Previous studies have found differences between women and men regarding drinking behaviour and concluded that women need a more multipart type of alcohol use disorder (AUD) treatment. This study aims to examine the differences in outcome between women and men who have completed public outpatient alcohol treatment. Methods A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…Relapse (n = 110) was defined as return to any alcohol consumption during the 3 months of acamprosate treatment, whereas non-relapse (n = 157) was defined as abstinence from alcohol (no alcohol use) during 3 months of acamprosate treatment (see Figure 1a). Baseline characteristics of the AUD participants in both groups are listed in AUD participants, two thirds were men, consistent with most studies of AUD-a disorder that displays a striking difference in incidence between the sexes (Blendberg et al, 2020;Erol & Karpyak, 2015).…”
Section: Characteristics Of Study Participantssupporting
confidence: 78%
“…Relapse (n = 110) was defined as return to any alcohol consumption during the 3 months of acamprosate treatment, whereas non-relapse (n = 157) was defined as abstinence from alcohol (no alcohol use) during 3 months of acamprosate treatment (see Figure 1a). Baseline characteristics of the AUD participants in both groups are listed in AUD participants, two thirds were men, consistent with most studies of AUD-a disorder that displays a striking difference in incidence between the sexes (Blendberg et al, 2020;Erol & Karpyak, 2015).…”
Section: Characteristics Of Study Participantssupporting
confidence: 78%
“…Third, this study only included male patients. Nevertheless, some studies have found sex differences in drinking behavior, neural systems, and AUD treatment ( 65 , 66 ). Schulte et al.…”
Section: Discussionmentioning
confidence: 99%